Auxilio Social and the education of the poors: from the Franco’s regime to the Spanish democracy (Foro de Educacion, 2024)
Next article explains the meaning that AS had from the Franco’s regi- me until the spanish democracy. A regime’s official organization in charge of giving assistance to the needy and spreading the education system prevailing in Spain those days. The study of the AS’s departments will allow us to know the kind of institutions that it established in the diferents stages of the Franco’s regime, the education that the assisted people were receiving in those institutions and the changes that this organi- zation experienced, specially about social assistance subject, with the arrival of the democracy.